2005
DOI: 10.1007/s10722-004-6110-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Genetic Diversity in the International Cocoa Genebank, Trinidad (ICG,T) using Isozyme Electrophoresis and RAPD

Abstract: Random amplified polymorphic DNA (RAPD) and isozyme electrophoresis (IE) techniques were used to estimate the level of genetic diversity in a sample of cacao germplasm existing at the International Cocoa Genebank, Trinidad. Twenty-six cocoa populations represented by 459 cocoa genotypes were analysed using IE and 22 populations represented by 353 cocoa genotypes were analysed using RAPD. Despite few differences in the classification of the populations, both techniques revealed three major groups: the indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
3
21
0
4
Order By: Relevance
“…Conversely, for seven other traits concerning the seeds and the fruit shape such as LG/WD, FS, WT and NS, the basin variance component was higher. In general, the partitioning of variation within and among populations (river basins) revealed that most variation was detected within populations, as in other studies with cacao tree, involving isozymatic (Ronning and Schnell, 1994;Sounigo et al, 1997) and RAPD (Russel et al, 1993) markers. Many other tree species have revealed the same pattern of variation distribution.…”
Section: Resultssupporting
confidence: 69%
“…Conversely, for seven other traits concerning the seeds and the fruit shape such as LG/WD, FS, WT and NS, the basin variance component was higher. In general, the partitioning of variation within and among populations (river basins) revealed that most variation was detected within populations, as in other studies with cacao tree, involving isozymatic (Ronning and Schnell, 1994;Sounigo et al, 1997) and RAPD (Russel et al, 1993) markers. Many other tree species have revealed the same pattern of variation distribution.…”
Section: Resultssupporting
confidence: 69%
“…Amostras de DNA de cada planta foram amplificadas por RAPD (Williams et al, 1990), em condições de amplificação e eletroforese previamente padronizadas (Freire et al, 2007). Foram utilizados iniciadores decâmeros dos kits OPA, OPB, OPC, OPD, OPH, dos quais 20 iniciadores por kit, cujas seqüências encontram-se em Operon Molecules for Life (2005).…”
Section: Methodsunclassified
“…Os marcadores genéticos RAPD (Williams et al, 1990), sozinhos ou em associação com outros marcadores moleculares, têm sido utilizados nos estudos da variabilidade genética entre acessos provenientes de bancos internacionais de germoplasma de cacau (Lerceteau et al, 1997;Marita et al, 2001;Faleiro et al, 2004c;Sounigo et al, 2005) e dos bancos de germoplasmas e cultivares brasileiros (Dias, 2001;Yamada et al, 2001Yamada et al, , 2003Santos et al, 2005). Algumas seleções das fazendas no Sul da Bahia foram caracterizadas com base em marcadores RAPD (Faleiro et al, 2004b;Yamada et al, 2005) e microssatélites (Faleiro et al, 2004a).…”
Section: Introductionunclassified
“…With the help of a 10× magnifying glass, and after a lateral incision on the ovary, the number of ovules was counted for each sampled flower per plant. The number of flowers per plant was nine per plant, the same adopted before to evaluate the Genetic distances, R1 and R2 represent genetically distinct branches based on the analysis by Neighbor Joining from RAPD and isoenzymes [13]. D1, D2, D3 represent three distinct quadrants on the bi-dimensional plan, related to the analysis of the dispersion of 270 cacao accesses of CEPEC's germplasm bank, based on RAPD markers [14].…”
Section: Methodsmentioning
confidence: 99%